Expressive Speech In “To All The Boys: Always And Forever” - Safira Ade Purnama; Ni Luh Putu Krisnawati; Novita Mulyana (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study explores how expressive speech acts are used in the teen romantic comedy movie